Pesantren in the Digital Era: Looking for the Chances and the Challenges - Abdul Muiz (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
This study aims to review the opportunities and challenges of pesantren in the digital era. As an Islamic educational institution that has survived for centuries, pesantren should adapt to the development of science and technology. Some of the questions that arise include: Do pesantrens have opportunities in the digital era? What are the challenges that must be faced in the digital era, and how do pesantrens negotiate the five pillars of Islamic boarding schools in the digital era? This study is a library research by looking at articles, journals, and scientific books related to Islamic boarding schools and their developments. By using descriptive analysis, this study shows that Islamic boarding schools can survive and adapt to the development of digital life and are able to develop better pesantren values through maximizing the use of technology and digital in teaching and learning activities to reach a wider community in general and become an inspiration for educational institutions domestically and internationally.